Pendampingan Kelompok Kecil Untuk Meningkatkan Kemampuan Guru Dalam Menerapkan Penilaian Autentik Di KKG MI Kecamatan Poncokusumo Kabupaten Malang - Rohmah, Tri Hidayati (Inovasi: Jurnal Diklat Keagamaan, 2020)
This research is based on the lack of application of authentic assessment in KKGMI, Kecamatan Poncokusumo. With authentic assessment, teachers can see the progress of students learning and the success level of the learning process which has been done. Authentic assessment instruments that can be used in the form of tests, observation rubrics, self-assessment, peer assessment, practice and others. The problems of this study are: [1] Whether the assistance of small groups can improve the teachers ability to apply authentic assessment in KKGMI Kecamatan Poncokusumo Kab. Malang ? and [2] How small group assistance can improve the teachers ability to apply authentic assessment in KKGMI, Kecamatan Poncokusumo Kab. Malang? While the purpose of this study is to improve the teachers ability to apply authentic assessment in KKG MI Kecamatan Poncokusumo Kab. Malang through the small group assistance. The method of this research was action research with small group assistance that was conducted in two cycles. Based on the results of the action research it can be concluded: the small group assistance had an effect on increasing the ability of MI teachers in the KKGMI target area of Kecamatan Poncokusumo in applying authentic assessment by comparing the observation value of documents applying authentic assessment in the RPP (lesson plan), the average value of Initial Conditions 63.5, First Cycle 71.5 and Second 76.5.